Exploring assessment methods used by Grade Four English First Additional Language Teachers - Kofi Nkonkonya Mpuangnan; Gladys Phumzile Mngomezulu; Samantha Govender (Journal of Modern Research in English Language Studies)
The form of assessment which grade four teachers use to determine the learning outcomes of the learners who are studying English First Additional Language (EFAL) in South African schools demands urgent attention. This urgency stems from the necessity to critically examine the post-apartheid educational system's assessment practices and how effectively they align with the evolving needs of society. To maintain a more discreet approach, this investigation specifically centered on teachers of EFAL and utilized a qualitative case study methodology. A purposive sampling technique led to the inclusion of 10 grade four EFAL teachers from schools in the King Cetshwayo District for data collection. The primary tool employed for this purpose was a semi-structured interview, skillfully developed to explore the perspectives of teachers and beliefs on assessment techniques. The researchers opted for a thematic analysis approach, allowing for a thorough examination of the data while respecting the privacy and confidentiality of the participants. The findings of classwork and teachers predominantly leaned towards traditional approaches such as engaging students through question-and-answer interactions, conducting tests, evaluating classwork, and assessing comprehension abilities. These methods were the primary means through which teachers assessed their students' understanding and performance within the learning environment. The study recommended that diversifying assessment techniques could provide a more comprehensive understanding of learners' development, catering to varying abilities and better addressing individual learning needs.